Decision Support System Scheme Using Forward Chaining And Simple Multi Attribute Rating Technique For Best Quality Cocoa Beans Selection - Januar Adi Putra; Agustinus Mariano Galwargan; Nelly Oktavia Adiwijaya (IAES Indonesia Section, 2018)
Cocoa is a crop plantation originating from the tropical forests of Central America and northern part of South America. In general, cocoa grouped into three types namely Forastero, Criollo, and Trinitario which is the result of a cross between Forastero with Criollo. Cocoa (Theobroma cacao L.) is one of the comodity that has an important role in the Indonesian economy. The Indonesian's processing directorate, and the programs related to the 2015-2019 development are the Increased Production and Productivity of Sustainable Plantation Crops. This program is conducted to increase the production, productivity of cocoa and other plantation crops. One of the focus activities is Inventory of postharvest data of plantation. In the selection of cocoa beans based on the best quality, Indonesian Coffee and Cocoa Research Center is often missed so that there are some cocoa beans that should not pass the quality but still processed into processed products. In that case we proposed a new scheme for Decision Support System by using Forward Chaining method and Simple Multi Attribute Rating Technique (SMART). The combination of these two methods proved to be able to do a very good selection of cocoa beans. Where the selection is done with two stages proven can really filter the cocoa beans are good for health.